Ceremonial Ayahuasca in Amazonian Retreats—Mental Health and Epigenetic Outcomes From a Six-Month Naturalistic Study - Ruffell, Simon G. D.; Netzband, Nige; Tsang, WaiFung; Davies, Merlin; Inserra, Antonio; Butler, Matthew; Rucker, James J. H.; Tófoli, Luís Fernando; Dempster, Emma Louise; Young, Allan H.; Morgan, Celia J. A. (Frontiers in Psychiatry, 2021)
Ayahuasca is a natural psychoactive brew, used in traditional ceremonies in the Amazon basin. Recent research has indicated that ayahuasca is pharmacologically safe and its use may be positively associated with improvements in psychiatric symptoms. The mechanistic effects of ayahuasca are yet to be fully established. In this prospective naturalistic study, 63 self-selected participants took part in ayahuasca ceremonies at a retreat centre in the Peruvian Amazon. Participants undertook the Beck Depression Inventory (BDI-II), State-Trait Anxiety Inventory (STAI), Self-Compassion Scale (SCS), Clinical Outcomes in Routine Evaluation – Outcome Measure (CORE-OM), as well as secondary measures, pre- and post-retreat and at 6-months. Participants also provided saliva samples for pre/post epigenetic analysis. Overall, a statistically significant decrease in BDI-II (13.9 vs 6.1, p<0.001), STAI (44.4 vs 34.3 p<0.001) scores, and CORE-OM scores were observed (37.3 vs 22.3 p<.001) at post-retreat, as well as a concurrent increase in SCS (3.1 vs 3.6, p<0.001). Psychometric improvements were sustained, and on some measures values further decreased at 6-month follow-up, suggesting a potential for lasting therapeutic effects. Changes in memory valence were linked to the observed psychometric improvements. Epigenetic findings were equivocal, but indicated that further research in candidate genes, such as sigma non-opioid intracellular receptor 1 (SIGMAR1), is warranted. This data adds to the literature supporting ayahuasca’s possible positive impact on mental health when conducted in a ceremonial context. Further investigation into clinical samples, as well as greater analyses into the mechanistic action of ayahuasca is suggested.